(3cJGH aj hbha GdbQBf hCLRGFg hJbSjeGJgs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdNGWi GdQGLi QMeI Gddg GdHGQi , eMeO Hf eMeO Hf Ydi Hf eMeO GdSeQbfOi GdgePGfi Gf Gddg bO CYWGfi HaVdg GdYeje fUjHkG ai Ydhe GdbQBf s
(3BNQgG (B:s
(3ef LeGYI cKjQI efge GHh YHO GdQMef YeQ Hf GdNWGH GdYOhi hef GdHUQI CHh GdeTLQ YGUe Hf GdYLGL QVi Gddg Yfge CLejYf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3bQGAGJ (B386) s
Keywords: (3GdbQGAGJ hGdJLhjOs